The Improvement of Physics Teachers’ Competence in Developing an Interactive Recitation Programs to Remediate Students’ Misconception - Sundari, Putri Dwi; Dewi, Wahyuni Satria; Saputra, Defrizal; Mairizwan, Mairizwan -; Hidayat, Rahmat (Universitas Islam Negeri Raden Intan Lampung, 2021)
During learning from home, the teacher is very limited in giving feedback on assignments. Consequently, students’ understanding of physics concepts is still low and experiencing misconceptions. Therefore, teachers should able to develop an interactive recitation program completed by corrective feedback that could remediate students’ misconceptions. The research objective is to improve the competence of physics teachers at Sijunjung Regency through mentoring in developing an interactive recitation program. This sort of research is quasi-experimental with one-group pretest-posttest design. The research data was obtained from the pretest and posttest about understanding of the interactive recitation programs. The results showed that there was an increase in the knowledge of high school physics teachers in understanding the interactive recitation program with a percentage of 32.4%, and the provision of mentoring activities have a significant effect on increasing the competence of physics teachers in developing interactive recitation programs.